Aggregation and fusion of low-density lipoproteins in vivo and in vitro - Lu, Mengxiao (2013)
Low-density lipoproteins (LDLs, also known as ‘bad cholesterol’) are the major carriers of circulating cholesterol and the main causative risk factor of atherosclerosis. Plasma LDLs are 20- to 25-nm nanoparticles containing a core of cholesterol esters surrounded by a phospholipid monolayer and a single copy of apolipoprotein B (550 kDa). An early sign of atherosclerosis is the accumulation of LDL-derived lipid droplets in the arterial wall. According to the widely accepted ‘response-to-retention hypothesis’, LDL binding to the extracellular matrix proteoglycans in the arterial intima induces hydrolytic and oxidative modifications that promote LDL aggregation and fusion. This enhances LDL uptake by the arterial macrophages and triggers a cascade of pathogenic responses that culminate in the development of atherosclerotic lesions. Hence, LDL aggregation, fusion, and lipid droplet formation are important early steps in atherogenesis. In vitro, a variety of enzymatic and nonenzymatic modifications of LDL can induce these reactions and thereby provide useful models for their detailed analysis. Here, we summarize current knowledge of the in vivo and in vitro modifications of LDLs leading to their aggregation, fusion, and lipid droplet formation; outline the techniques used to study these reactions; and propose a molecular mechanism that underlies these pro-atherogenic processes. Such knowledge is essential in identifying endogenous and exogenous factors that can promote or prevent LDL aggregation and fusion in vivo and to help establish new potential therapeutic targets to decelerate or even block these pathogenic reactions.